2015
DOI: 10.1016/j.progress.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Retail development in Turkey: An account after two decades of shopping malls in the urban scene

Abstract: The social, economic and environmental impacts of large-scale retail outlets on existing retail and urban systems have been extensively discussed in the planning literature. This article documents the last two decades of transformation in Turkey's retail sector, which have been characterized by a more organized development of the sector than traditionally existed. We begin our analysis with the late 1980s and early 1990s, when more-liberal and outward-looking policies began to emerge in Turkish economic policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 41 publications
(64 reference statements)
1
33
0
4
Order By: Relevance
“…The first period between 1990 and 2000 has witnessed the rise of shopping malls, especially in large cities. In the second period between 2000 and 2010, these malls have evolved into more complex marketspaces, and shopping mall investments have extended to smaller cities (Erkip & Ö züduru, 2015). The timing of these periods may be associated with economic liberalization policies and -of course-global trends.…”
Section: A Brief Overview Of Turkish Retail Industrymentioning
confidence: 99%
“…The first period between 1990 and 2000 has witnessed the rise of shopping malls, especially in large cities. In the second period between 2000 and 2010, these malls have evolved into more complex marketspaces, and shopping mall investments have extended to smaller cities (Erkip & Ö züduru, 2015). The timing of these periods may be associated with economic liberalization policies and -of course-global trends.…”
Section: A Brief Overview Of Turkish Retail Industrymentioning
confidence: 99%
“…Yu et al [48] reported that, although development of local large-scale shopping centers in suburbs and along arterial roads increase citizens' quality of life in terms of shopping convenience, it increases city sprawl and generates high car traffic. Thus, excessive retail development may increase pollution and greenhouse gas emissions [49]. Therefore, we recommend spatial planning that balances regeneration of inner city shopping centers and development of new commercial centers in suburban areas; such planning would optimize urban spatial structure, which, in turn, can effectively reduce carbon emissions.…”
Section: Location and Transport Carbon Emissionsmentioning
confidence: 99%
“…According to a recent report, the number of shopping malls, which was 12 in 1995, reached 400 as of July 2017 [28]. The increase in population and income, the changing leisure and consumption patterns, the modernity provided by the shopping malls and macro-level changes in the political, economic and social environments of Turkey are seen as the main reasons for this significant increase in the number of shopping malls [25,26,[29][30][31]. As stated by Tabak et al [25], these developments are still continuing and creating a severe competition in the sector.…”
mentioning
confidence: 99%
“…As stated by Tabak et al [25], these developments are still continuing and creating a severe competition in the sector. In this framework, investigating the most suitable location for shopping centers represents a difficult task for investors in Turkey [30].Furthermore, from the sustainable development perspective, the economic, environmental and social impacts of shopping malls' locations on retail and urban systems have been well recognized especially in the urban planning literature [29,32,33]. The economic dimension of sustainable development simply indicates that the location of a shopping mall should make it possible to achieve and sustain high profitability in the long term.…”
mentioning
confidence: 99%
See 1 more Smart Citation